Perbandingan Sistem Pemilihan Presiden Indonesia Dengan Turki - Zamili, Ester; Dompak, Timbul (Prosiding, 2024)
This research compares the presidential election systems between Indonesia and Türkiye with a focus on differences in electoral systems and election processes. Indonesia applies a direct election system where the people elect the president, while Turkey uses a system where the president is elected by parliament. The research results show that voter participation tends to be higher in Indonesia, while Turkey has a presidential election process through parliament. In addition, Indonesia has more open and accountable practices in the presidential election process compared to Türkiye. The role of electoral institutions such as the KPU in Indonesia and YSK in Türkiye also shows differences in authority and independence. A deep understanding of these differences provides valuable insight into the development of political systems and presidential elections in both countries.